Efficacy and Safety of Rivaroxaban as Thromboprophylaxis after Arthroplasty of the Hip or Knee (Medical Forum Monthly, 2024)
Objective: to investigate efficacy and safety of rivaroxiban as thromboprophylaxis in major orthopedic surgeries.Study Design: Non randomized experimental trial studyPlace and Duration of Study: This study was conducted at the department of orthopedic surgery, Bahawalpur Victoria Hospital, Bahawalpur, from April 2017 to April 2018.Materials and Methods: Adult patients of age limit from 20 to 45 years who were selected for hip and knee arthroplasty and who were given Rivaroxiban 10 mg were included in the study. Three main outcome variables were investigated: VTE confirmed through imaging, major bleed and death. SPSS version was used to analyze data. P value ≤ 0.05 was considered as significant.Results: A total number of 32 patients included in this study. Our results show that no patient was died during rivaroxiban treatment in our study duration but VTE was observed in 6% of cases and major bleed was observed in 15% of cases. Except these major variables mean age, hemoglobin, platelets, PT, APTT, urea, creatinine and bilirubin of the patients was 45.50±0.71 years, 103.51±2.12 g/l, 227.0±0.21×109/l, 13.50±2. 14s,23.50± 4.51s,4.50±1.78mmol/l, 68.0±2.83 µmol/l and 11.50±2.57 µmol/l respectivelyConclusion: Results of our study revealed that rivaroxiban is a safe drug as mortality is zero during its treatment and its is also effective as it’s reduce the incidence of VTE and major bleeding when used as thromboprophylaxis during surgery of hip arthroplasty and knee arthroplasty.